Pricing under Spatial Competition and Spatial Monopoly - Capozza, Dennis R.; Order, Robert Van (Econometrica, 1977)
[Research on the spatial firm has shown that spatial results often differ from non-spatial. This paper considers the relationship between the price of a spatial monopoly and the price of a spatially competitive firm. The conditions under which the competitive price will exceed the monopoly price are outlined.]